THE DESIGNER BETWEEN TECHNIQUE AND THE MARKET: CONCEPTUAL INDEFINATIONS AND FORMATIVE PATHS - Studart, Freddy; de Figueiredo , Ana Valeria; Siqueira, Isabella Ferreira (Seven Editora, 2026)
This article proposes a critical reflection on the multiple meanings attributed to the profession of designer, emphasizing the formative challenges and the conceptual and institutional uncertainties surrounding its practice. Using graphic design as an example, it discusses how this practice articulates technical, creative, symbolic, and market dimensions. The qualitative investigation is based on a bibliographic and documentary review, encompassing legislation, occupational classifications, and academic publications. By analyzing the tensions between formal and non-formal training, the impacts of technological transformations, and the demands of the job market, the text seeks to understand how professionals construct their career paths in a scenario of constant reinvention. It concludes that design, more than a technical activity, constitutes a plural and dynamic field, traversed by symbolic disputes and complex social demands, requiring critical perspectives and adaptive formative strategies.DOI: https://doi.org/10.56238/sevened2026.001-018